THE INFLUENCE OF SERVICE QUALITY AND PRICES OF SERVICES ON CUSTOMER SATISFACTION - Natigor, Dayan Hakim; Khoiruddin, Muhammad Rifqi (IKRAITH-EKONOMIKA, 2026)
Udinrace car repair shop is a car repair shop that operates in the services and marketing sector, which is currently pioneering and is located in Bojongsoang, Bandung Regency. Globalization has had a huge impact on the development of the business world throughout the world. The market is getting wider and the business world is getting wider. But on the other hand, competition is getting tighter and more difficult. Conditions like this require companies to be competitive and have superior products or services compared to competitors who are involved in the same business. This research aims to determine the influence of service quality and price on customer satisfaction at the Udincare car repair shop. The research method used in this research is a quantitative research method with a descriptive and verification approach. The data used is primary data. Data collection uses library research and documentation obtained from the city of Bandung and previously purchased. Sampling used a non-probability sampling method with a purposive sampling method and data was obtained for 100 samples. The data collection technique carried out by the author was to collect the data by distributing questionnaires to respondents and literature study using data analysis techniques using classical assumption tests, multiple regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. Descriptive research results show that Customer Satisfaction is in the very good category, Service Quality is in the very good category and Sales Promotion is in the very good category